JUDICIAL REVIEW SEBAGAI SARANA PERLINDUNGAN HAK-HAK ASASI WARGA NEGARA - Safi’, Safi’ (DiH: Jurnal Ilmu Hukum, 2015)
Observing the development of public acceptance of the substance of the laws that were generated in recent time, the right of judicial review of an option that can not be avoided for the 'correct' errors that might occur in a legal product to guarantee the protection of constitutional rights of citizens. The tendency in this direction can be seen from the desire of some community groups to apply for judicial review and claim that they are legal products containing controversial value both to the Supreme Court nor the Constitutional Court. If prior to the amendment of the 1945 Constitution, laws and regulations that can be petitioned for review of material just under the Act against the Constitution, but after the 1945 amendment, the legislation level as the Act was that the Act and also Perpu material can be petitioned for review to the Constitutional Court.